2016
DOI: 10.1590/s1984-29612016003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against Neospora spp. and Sarcocystis neurona in donkeys from northeastern Brazil

Abstract: Sarcocystis neurona and Neospora hughesi are coccidian protozoa that can cause neurological illness in horses in America. In this study we report seroprevalence of Neospora spp. andS. neurona in sera of 333 donkeys from the northeastern region of Brazil. Antibodies to Neospora spp. were detected in 2% (7 donkeys) of 333 sera tested by the indirect fluorescent antibody test (IFAT) with a cut-off dilution of 1:40. Antibodies to S. neurona were found in 3% (10 donkeys) of the samples tested by IFAT (cut-off ≥50) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…This seroprevalence is comparable with a 2% seroprevalence of Neospora reported in 333 donkeys from the north-eastern region of Brazil using IFAT (cut-off 1:40) [7]. In another study in Brazil, researchers found antibodies to Neospora in 2 of 500 donkeys studied using IFAT (cut-off 1:100) [6].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This seroprevalence is comparable with a 2% seroprevalence of Neospora reported in 333 donkeys from the north-eastern region of Brazil using IFAT (cut-off 1:40) [7]. In another study in Brazil, researchers found antibodies to Neospora in 2 of 500 donkeys studied using IFAT (cut-off 1:100) [6].…”
Section: Discussionsupporting
confidence: 70%
“…Sera of 333 donkeys from four states in Brazil were tested for antibodies to S. neurona by using the indirect fluorescent antibody test (IFAT, cut-off 1:40) and direct agglutination tests (SAT, cut-off 1:50). Ten (3.0%) were seropositive by IFAT and 69 (21.0%) were positive by SAT [7]. However, comparison of these seroprevalences should be interpreted with care since different laboratory methods were used to detect anti- S. neurona antibodies among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Equine emerging tick-borne neurological diseases has been reported in donkeys (because tick bites are highly prevalent in this species due to their common extensive management). Neosporosis has been described all over the world, from Europe [92] to South America [93,94]. Lyme disease (Borrelia spp.)…”
Section: Neurologymentioning
confidence: 99%
“…A recent study reported the results of serological survey of antibodies against S. neurona in sera of 333 donkeys from the northeastern region of Brazil (Alagoas, Paraíba, Pernanbuco, Piauí and Rio Grande do Norte). Antibodies to S. neurona were found in ten donkeys (3%) of the samples tested by IFAT and in 69 donkeys (21%) by the direct agglutination test (SAT) (GENNARI et al, 2016). The SAT and IFAT results for S. neurona showed a poor concordance in this study, which might be due to the lack of a comprehensive study of sensitivity and specificity of the SAT in equids (DUBEY et al, 2001a(DUBEY et al, , 2015b and lack of knowledge about cross-reactivity in both tests with other protozoa that can infect donkeys (GENNARI et al, 2016).…”
Section: Epidemiology In Brazilmentioning
confidence: 99%